2023
DOI: 10.4014/jmb.2212.12009
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of S-Adenosylmethionine Synthetase in Recombinant Chlamydomonas for Enhanced Lipid Production

Abstract: Microalgae are attracting much attention as promising, eco-friendly producers of bioenergy due to their fast growth, absorption of carbon dioxide from the atmosphere, and production capacity in wastewater and salt water. However, microalgae can only accumulate large quantities of lipid in abiotic stress, which reduces productivity by decreasing cell growth. In this study, the strategy was investigated to increase cell viability and lipid production by overexpressing S-adenosylmethionine (SAM) synthetase (SAMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…DSC was used to clarify the boundaries of the phase region and to reveal the water content of the hydrogel in different states (freezing-bound water, non-freezing water). [33] The above water state depends on the degree of interaction within the hydrogel structure. In this research, non-freezing bound water is closely associated with ions (Li + , Cl − ) through hydration and with polymers via hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…DSC was used to clarify the boundaries of the phase region and to reveal the water content of the hydrogel in different states (freezing-bound water, non-freezing water). [33] The above water state depends on the degree of interaction within the hydrogel structure. In this research, non-freezing bound water is closely associated with ions (Li + , Cl − ) through hydration and with polymers via hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…It is also chemically stable and easily processable. [82][83][84][85][86] It gives permeable and hydrophilic interfaces with body tissue, [87] provides incomparable physical, chemical, and thermal properties, [88] along with good ionic conductivity [89] and protecting agent. [86] PVA, at com-plete decomposition, produces water (H 2 O), and carbon dioxide (CO 2 ).…”
Section: Structural Modification Of Chitosanmentioning
confidence: 99%
“…[142] The temperature sensitive hydrogels have three types: a) negative temperature, b) positive temperature, and c) thermally reversible. Kim et al [84] synthesized chitosan and PVA based hydrogels and observed the temperature responsive behavior of the developed hydrogels, as these samples swelled at high temperature and de-swelled when temperature was lowered down. Such hydrogels are called positive temperature hydrogels, which exhibit upper critical solution temperature.…”
Section: Thermo-responsive Hydrogelmentioning
confidence: 99%
See 2 more Smart Citations